The Statewide Economic Impact of Child Care–Associated Viral Acute Gastroenteritis Infections. (19th June 2021) - Hayashi, Michael A L; Eisenberg, Joseph N S; Martin, Emily T; Hashikawa, Andrew N
Abstract: Introduction: More than 65% of children aged ≤5 years in the United States require out-of-home child care. Child care attendance has been associated with an elevated risk of respiratory illness and acute gastroenteritis (AGE). While child care–associated respiratory disease cases are more numerous, AGE is associated with more severe symptoms and more than double the number of absences from child care. In addition, viral pathogens such as norovirus, rotavirus, and adenovirus are highly infectious and may be spread to parents and other household members. As a result, child care–associated viral AGE may incur substantial economic costs due to healthcare service usage and lost productivity. Methods: We used surveillance data from a network of child care centers in Washtenaw County, Michigan, as well as a household transmission model to estimate the annual cost of child care–associated viral AGE in the state of Michigan. Results: We estimated that child care–associated viral AGE in Michigan costs between $15 million and $31 million annually, primarily due to lost productivity. Conclusions: The economic burden of child care–associated infections is considerable. Effective targeted interventions are needed to mitigate this impact.